Founding family ownership and the agency cost of debt - Anderson, Ronald C.; Mansi, Sattar A.; Reeb, David M. (Journal of Financial Economics, 2003)
We investigate the impact of founding family ownership structure on the agency cost of debt. We find that founding family ownership is common in large, publicly traded firms and is related, both statistically and economically, to a lower cost of debt financing. Our results are consistent with the idea that founding family firms have incentive structures that result in fewer agency conflicts between equity and debt claimants. This suggests that bond holders view founding family ownership as an organizational structure that better protects their interests.